Simultaneous Determination of Catalpol, Aucubin, and Geniposidic Acid in Different Developmental Stages of Rehmannia glutinosa Leaves by High Performance Liquid Chromatography - Yanjie Wang; Dengqun Liao; Minjian Qin; Xian’en Li (Journal of Analytical Methods in Chemistry)
Although R. glutinosa roots are currently the only organ source in clinics, its leaves are a potential supplement for the roots especially in extraction of some important bioactive compounds. Our early work found that the contents of catalpol and total iridoid glycosides varied among different developmental stages of R. glutinosa leaves. Aucubin and geniposidic acid, the abundant major bioactive compounds in Eucommia ulmoides and Gardenia jasminoides, respectively, were found present in R. glutinosa roots, however, and have not been analyzed in its leaves. In this paper, we aimed to determine contents of these three iridoid glycosides in different developmental stages of R. glutinosa leaves using the optimized HPLC-UV conditions. Our results showed that aucubin and GPA in R. glutinosa leaves were much lower than catalpol and showed the increasing trend with the leaf development, which was different from catalpol. This work provided the important information for future exploitation of R. glutinosa leaves as a potential supplement for its roots in extraction of some important bioactive compounds and studying the relationship of aucubin and catalpol metabolism.